2017
DOI: 10.1097/ico.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

CYP1B1 Cytopathy: Uncommon Phenotype of a Homozygous CYP1B1 Deletion as Internal Corneal Ulcer of Von Hippel

Abstract: We present an uncommon mutation and clinical description of CYP1B1. This report and further studies could provide us better understanding of the mutational spectrum of CYP1B1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Because the outcomes of PK were poor in this report, they proposed that different pathogenic variants of CYP1B1 may have a distinct prognostic value. 6 Edward et al 2 also suggested that modifiers of the ocular phenotype can either mitigate or worsen the effects of CYP1B1 variants, thus explaining the co-occurrence of PCG, PA, and a normal ocular phenotype in relatives with homozygous CYP1B1 variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the outcomes of PK were poor in this report, they proposed that different pathogenic variants of CYP1B1 may have a distinct prognostic value. 6 Edward et al 2 also suggested that modifiers of the ocular phenotype can either mitigate or worsen the effects of CYP1B1 variants, thus explaining the co-occurrence of PCG, PA, and a normal ocular phenotype in relatives with homozygous CYP1B1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…CYP1B1 has been also linked to a particular phenotype of CCO, described as “ CYP1B1 cytopathy.” 5,6 The term refers to a phenotype characterized by raised intraocular pressure (IOP) and limbus-to-limbus avascular corneal opacity, which do not resolve with glaucoma control. The histopathology was reported as showing central absence of Bowman layer, Descemet membrane, and endothelium, with no Haab striae.…”
mentioning
confidence: 99%